Strategi dan Implementasi Pembiayaan Kepemilikan Rumah dengan Akad Murabahah pada Bank Syariah Mandiri Cabang Samarinda - Yuliani, Irma (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The research is motivated by increasing population and demand community to meet housing needs. Related to this, how is the Bank's Strategy Syariah Mandiri Samarinda Branch as one of the banks that has an important role as Intermediary institutions, to realize the desire of customers to have decent housing through its products are Griya BSM and How to Implement Home Ownership financing with The Murabahah Agreement is in the context of achieving company goals amid the bank’s world competition increasingly sharp. This type of research is field research, which is a study carried out systematically by lifting data in the field. The purpose of this research is to find out the Strategy and Implementation of Home Ownership Financing With Murabahah Agreement at Bank Syariah Mandiri Samarinda Branch. The nature of the research this is Descriptive Qualitative. The research uses observation, interview and documentation techniques with management resource persons / related bank parties.The research uses Analysis of Miles And Hubberman. The results of the research, it was found that BSM determined the segmentation of BSM Griya products based on demographic segmentation which is based on income level and employment level. Determination of market targeting on BSM Griya products, through two categories, namely permanent employees such as civil servants and professional jobs such as doctors or equivalent. Positioning Griya BSM products in the minds of consumers is the Sharia brand itself, flat installments, speed and accuracy of the process, and fewer costs incurred by customers than conventional home financing. The results of the research indicate that the strategies carried out by the Mandiri Branch Syariah Bank Samarinda is determining Segmentation, namely dividing customers based on income level and job, Positioning that is offering superior products that have unique and sharia values, and Targeting is aiming at fixed income customers by cooperating with agencies and doing individual prospects. In order for the strategy to be achieved, the marketing mix is carried out includes 4 P namely Product, Price, Place, and Promotion which done by displaying the uniqueness of the product, affordable prices with flat installments and low margin compared to other banks, convenient service locations, and promotional uses reference of friends of BSM, advertisements, brochures, social media, sticking to running advertisements as well as collaborate and presentations to government and private agencies and individuals. Implementation of home ownership financing is carried out through 4 stages namely : submission of application, inspection and analysis, signing of agreement and disbursement. Procedure stages based on 5 C (Character, Capital, Capability, Collateral, and Condition of Economy) with the most disbursement time 1 week long and using a Murabahah contract with flat / fixed installments, Fixed an 11% margin,mild down payment, and free final.